Effect of Electrical Treatment of Seed Tubers on the Growth, Development, and Yield of Potato Cultivars - Samaridinovich, Qo‘chqorov Nasriddin (American Journal of Botany and Bioengineering, 2025)
The study was conducted to investigate the effects of electrical treatment applied to seed tubers on the growth, development, yield, product quality, and seed-tuber characteristics of potato cultivars. Analytical results showed that pre-planting electrical exposure accelerated sprouting by 3–4 days depending on the variety, increased plant height by 3–7 cm, and raised the number of stems per plant by 0.3–0.4. Electrical treatment also expanded the assimilation surface area by up to 2000 m² per hectare, reduced the expression of viral disease symptoms, and ensured an additional yield of 2.6–3.5 tons per hectare.